Pengembangan Media STEMTora pada Pembelajaran IPAS di Sekolah Dasar Materi Transformasi Energi - Machdalena, Maya; Suhartini, Erna; Haerani, Rosita Putri Rahmi (Universitas PGRI Semarang, 2025)
This study aims to develop and evaluate the feasibility of an interactive learning media based on Lectora Inspire integrated with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in the subject of Natural and Social Sciences (IPAS) at the elementary school level, specifically focusing on the topic of Energy Transformation in Grade IV. The research employed a Research and Development (RD) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews and questionnaires, using instruments such as expert validation sheets (content and media experts) and response questionnaires for teachers and students. The validation results indicated a high level of validity, with 87.5% from the content expert and 88.5% from the media expert. The small-scale trial showed a positive student response of 89%, while the large-scale trial yielded a response of 92.8%. Based on these findings, it can be concluded that the interactive learning media developed with Lectora Inspire and the STEAM approach is feasible for use and received highly favorable responses from users.